2016
DOI: 10.5941/myco.2016.44.3.180
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Association ofTrichoderma asperellumwithinTheobroma cacaoSuppresses Vascular Streak Dieback Incidence and Promotes Side Graft Growth

Abstract: Trichoderma species are able to persist on living sapwood and leaves of cacao (Theobroma cacao) in an endophytic relationship. In this research, we evaluated the ability of Trichodema asperellum introduced at the incision site in the bark for side grafting with the concentration of 4 g/10 mL, 4 g/100 mL, and 4 g/1,000 mL (suspended in water) in suppressing vascular streak dieback (VSD) incidence and promoting growth of side grafts in the field. The incidence of VSD in two local clones of cacao, MCC1 and M04, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
(30 reference statements)
0
12
0
1
Order By: Relevance
“…We do not know what supports this phenomenon, but Trichoderma is capable of growing and developing in composted plant residues [18], probably increasing the likelihood of penetrating and deploying in cacao tissues, and on the other hand, Trichoderma can degrade the compost making it available to root systems. Therefore, our results offer new insight to the application of the biological agent T. asperellum in combination with composted residues through soil amendment, because, since its discovery in the early 2000s in South Sulawesi [3], there has been no method capable of controlling the VSD disease effectively. An unpublished trial of flutriafol fungicide with the same clone used in this experiment resulted in a small impact on the reduction of VSD incidence.…”
Section: Discussionmentioning
confidence: 87%
“…We do not know what supports this phenomenon, but Trichoderma is capable of growing and developing in composted plant residues [18], probably increasing the likelihood of penetrating and deploying in cacao tissues, and on the other hand, Trichoderma can degrade the compost making it available to root systems. Therefore, our results offer new insight to the application of the biological agent T. asperellum in combination with composted residues through soil amendment, because, since its discovery in the early 2000s in South Sulawesi [3], there has been no method capable of controlling the VSD disease effectively. An unpublished trial of flutriafol fungicide with the same clone used in this experiment resulted in a small impact on the reduction of VSD incidence.…”
Section: Discussionmentioning
confidence: 87%
“…They discovered that all four Trichoderma harzianum and T. viride inoculum densities increased tomato plant growth especially at the maximum density of 10 10 spores g − 1 soil. Rosmana et al [43] found that treatment with various concentrations of Trichoderma asperellum increased the numbers of Theobroma cacao buds and branches by 90.7 and 21.7%, respectively, relative to the control. Earlier research demonstrated inconsistent results for the effects of T. harzianum and T. viride on tomato plant growth [44].…”
Section: Effects Of Dse or T Viride Alone On The Growth Of Licorice mentioning
confidence: 99%
“…For inoculum preparation, a sterilized plastic bag containing around 100 g of rice grain medium was inoculated by the fungus of 7-day culture in PDA medium origin. Then, after seven days incubation at a temperature of 26°C-28°C and humidity of 80%-90%, Trichoderma was harvested, dried, and milled to form a smooth powder (Rosmana et al, 2016).…”
Section: Preparation Of T Asperellum Inoculum Compost and Mulchmentioning
confidence: 99%